6z+7=4z+2+z

Simple and best practice solution for 6z+7=4z+2+z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6z+7=4z+2+z equation:


Simplifying
6z + 7 = 4z + 2 + z

Reorder the terms:
7 + 6z = 4z + 2 + z

Reorder the terms:
7 + 6z = 2 + 4z + z

Combine like terms: 4z + z = 5z
7 + 6z = 2 + 5z

Solving
7 + 6z = 2 + 5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5z' to each side of the equation.
7 + 6z + -5z = 2 + 5z + -5z

Combine like terms: 6z + -5z = 1z
7 + 1z = 2 + 5z + -5z

Combine like terms: 5z + -5z = 0
7 + 1z = 2 + 0
7 + 1z = 2

Add '-7' to each side of the equation.
7 + -7 + 1z = 2 + -7

Combine like terms: 7 + -7 = 0
0 + 1z = 2 + -7
1z = 2 + -7

Combine like terms: 2 + -7 = -5
1z = -5

Divide each side by '1'.
z = -5

Simplifying
z = -5

See similar equations:

| 7(q-83)=63 | | 12xX=310 | | -33+90-22-9= | | 8x-15=4x-1 | | 18=2k+2 | | 0=4x-33 | | 9w-45=8w-24 | | 5.7x-15.1+4.3x=6.4+11x | | 13-3x=5x+8-7x | | -4x+6+5x=14-26 | | -4/9w=1/6 | | 22x-5-12x+3=24x-6-14x+17 | | 21-1=51 | | 7(x-4)(x-4)-3(x+5)(x+5)=4(x+1)(x-1)-2 | | 12z=9z-8z+2z | | 8x-35=6x-9 | | 4q-17=44 | | 5y-6+y+34=5y+40-3y | | 45=2x-2 | | 13y=12y-2/3 | | 9x+15+14-50=180 | | Y-3/1-y=3 | | 5.8+1.2x=2.2x | | -0.6w-17=0.1w+2.5 | | 3-5=2x-3 | | 4-6m/4m=3 | | x(x)=y-1 | | 5/15x10 | | x+x=1y | | 18-4=8-2(1+8n) | | 18.69=1.68e | | 3b-8=10+3 |

Equations solver categories